Imaging Pancreatic Beta-Cells: Update from the 4th Workshop of the National Institutes of Health, Washington DC, April 2009 (The Review of Diabetic Studies, 2023)
There is a crucial need for developing clinically useful approaches to measure pancreatic islet mass and function. Islets represent a small percentage of the tissue located in the abdominal cavity. They remain difficult to study in vivo by non-invasive techniques due to the lack of a specific probe. Also, it is difficult to correlate imaging signals and changes in beta-cell mass. Development of new and reliable cell markers are currently in progress. A major issue for the immediate future, is to gain a better understanding of the mechanisms leading to diabetes, and to increase the possibilities for studying islet function in vivo. Once diabetes occurs, islet transplantation is an option. However, the fate of the graft over time remains difficult to follow, due to the lack of tools to monitor rejection and inflammation before islet graft loss. The aim of this workshop was to gather the current knowledge on beta-cell imaging, including cross-linking to other field as oncology and neuroimaging.